Towards new NIR dyes for free radical photopolymerization processes - Mokbel, Haifaa; Noirbent, Guillaume; Gigmes, Didier; Dumur, Frédéric; Lalevée, Jacques (Beilstein Journal of Organic Chemistry, 2021)
The use of cheap and safe near-infrared (NIR) light is still the subject of intense research efforts but remains a huge challenge due to the associated low photon energy (wavelength from 0.78 to 2.5 µm). In this study, a series of 17 NIR dyes mainly based on a well-established cyanine scaffold is proposed. Remarkably, 11 of them were never synthesized before. Markedly, noncharged structures, negatively charged cyanine bearing Na+ as counter cation, and positively charged cyanines bearing (B(Ph)4−) or (I−) as counter anions were examined as promising NIR light photoinitiating systems. Excellent photoinitiating abilities were found for some reported dyes when used in combination with iodonium salt and amine. Markedly, photothermal effects with a huge heater behavior were also observed for different NIR dye structures. Interestingly, the synthesis of interpenetrating polymer networks (IPNs, e.g., for the polymerization of acrylate/epoxy monomer blends) can also be carried out upon NIR light with the proposed systems.
Keywords: cyanine; NIR light; photochemistry